Autoestima y actitud hacia la sexualidad en los adultos mayores de la parroquia San Antonio de las Aradas periodo 2022-2023 - Moreno Cumbicus, Jessica Katerine (2023)
Commonly, the Senescence has been considered the end of sexuality in older adults. During this period, large and diverse physical and psychological changes take place, which can affect self-esteem and therefore influence in the attitude of older adults towards their sexuality. The present investigative job had as objective determine the relationship that self-esteem has with attitudes towards sexuality in the older adults of San Antonio de las Aradas Parish. The study had a quantitative approach of correlational descriptive design. The sample was consisted of 60 older adults chosen by sampling non-probabilistic convenience, under the application of inclusion and exclusion criteria. For data collection we used the Questionnaire Attitudes Towards Sexuality in Old Age (CASV) and the Coopersmith Self-esteem Scale Adult Version (SEI). The results of the study indicate that the majority of older adults of the parish have a moderately high level of self-esteem and a positive attitude towards their sexuality. Furthermore, a moderate positive correlation was found between self-esteem and the attitudes towards the sexuality, suggesting that a higher level of self-esteem is associated with an attitude most positive towards the sexuality. Consequently, a promotion plan was developed to improve self-esteem and the attitudes towards the sexuality in this population